Feasibility and Outcomes of a Multidisciplinary Care Pathway for Neurogenic Thoracic Outlet Syndrome: A Prospective Observational Cohort Study. (June 2021) - Pesser, Niels; Goeteyn, Jens; van der Sanden, Lieke; Houterman, Saskia; van Alfen, Nens; van Sambeek, Marc R.H.M.; van Nuenen, Bart F.L.; Teijink, Joep A.W.
Abstract : Objective: The North American Society for Vascular Surgery (SVS) reporting standards for neurogenic thoracic outlet syndrome (NTOS) were published in 2016 to produce consistency in the diagnosis and treatment of NTOS, but outcomes resulting from following these standards are not yet available. The results of a standardised multidisciplinary care pathway for NTOS based on the North American SVS reporting standards for NTOS are reported. Methods: Patients referred between August 2016 and December 2019 with suspected NTOS were evaluated in this single center prospective cohort study. Diagnosis and treatment were performed according to a care pathway based on the North American SVS reporting standards. The outcome of surgically treated patients was determined by the Derkash score, thoracic outlet syndrome disability scale (TDS), Cervical Brachial Score Questionnaire (CBSQ), Disability of the Arm Shoulder and Hands Dutch language version (DASH-DLV) and Short Form-12 (SF-12) at three, six, 12, and 24 months. Results: Of 856 referred patients, 476 (55.6%) patients were diagnosed with NTOS. Dedicated physiotherapy was successful in 186 patients (39.1%). Surgical treatment was performed in 290 (60.9%) patients of whom 274 were included in the follow up. At a mean follow up of 16.9 ± 9.2 months, significant improvement ( p < .001) in TDS, CBSQ, DASH-DLV, and SF-12 scores was seen in the surgical group between baseline and all follow up intervals. Derkash outcome after surgical intervention was excellent in 83 (30.3%), good in 114 (41.6%), fair in 43 (15.7%), and poor in 34 (12.4%) of the patients. Complications occurred in 16 (5.8%) patients, and 32 (10.4%) patients experienced recurrent or persistent NTOS complaints. Conclusion: A multidisciplinary care pathway based on the North American SVS reporting standards for NTOS helped to confirm the diagnosis in 56% of patients referred, and guided the selection of patients who might benefit from thoracic outlet decompression surgery after unsuccessful dedicated physiotherapy. Intermediate follow up showed good outcomes in the majority of surgically treated patients.